Cooperative Learning Strategy of Think-Pair-Share (TPS) Technique to Improve Reading Comprehension Ability of The Middle School Students - Doni Sudibyo; Nurteteng Nurteteng (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The objective of this research is to find out whether or not the use of cooperative learning Think-Pair-Share in teaching reading able to improve the students reading comprehension ability of the middle school students. The sample of this study is the students in SMP IT Nurul Yaqin Sorong, west Papua there are 60 students, it consisted of 2 parallel classes; each class consisted of 30 students. The method used in this research was quasi-experimental method, here the writer uses two classes as sample, namely experimental class and control class. Based on the findings, it concludes that need analysis is the means of total score for post-test of experimental class and control class one was different. Where the t-test value is greater (6.178) than the t-table value (2.00) for 0.05 level of significance, degree of freedom (N1+N2-2) 58. This means that the achievement of the students who were thought rerated through cooperative learning in reading comprehension is different. Thus, the alternative hypothesis saying that there is significant difference in reading achievement between students learning reading by using cooperative learning and without using cooperative learning.